2010
DOI: 10.1038/jhg.2010.71
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of longevity-associated mitochondrial DNA 5178 C/A polymorphism and coffee consumption on the risk of hyper-LDL cholesterolemia in middle-aged Japanese men

Abstract: The objective of this study was to investigate whether the mitochondrial DNA 5178 cytosine/adenine (Mt5178 C/A) polymorphism modifies the effects of coffee consumption on serum lipid levels and the risk of dyslipidemia in middle-aged Japanese men. A total of 397 male subjects (age, 53.9±7.8 years; mean±s.d.) were selected from among individuals visiting the hospital for regular medical check-ups. After adjustment for age, body mass index, habitual alcohol consumption, habitual smoking and use of antihypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The present study shows that coffee consumption may decrease the number of CRF components among Mt5178C genotypic men, and previous studies have reported that coffee consumption decreases the risk of hypertension [10] and AGT [12]. On the other hand, the present study shows that coffee consumption may increase the number of CRF components among Mt5178A genotypic men, and a previous study reported that coffee consumption increases the risk of hyper-LDL cholesterolemia among Mt5178A genotypic men [11]. The present study shows a U-shaped association between the frequency of alcohol consumption and the clustering of CRFs among Mt5178C genotypic men.…”
Section: Discussionsupporting
confidence: 85%
“…The present study shows that coffee consumption may decrease the number of CRF components among Mt5178C genotypic men, and previous studies have reported that coffee consumption decreases the risk of hypertension [10] and AGT [12]. On the other hand, the present study shows that coffee consumption may increase the number of CRF components among Mt5178A genotypic men, and a previous study reported that coffee consumption increases the risk of hyper-LDL cholesterolemia among Mt5178A genotypic men [11]. The present study shows a U-shaped association between the frequency of alcohol consumption and the clustering of CRFs among Mt5178C genotypic men.…”
Section: Discussionsupporting
confidence: 85%
“…Previous cross-sectional studies reported the joint effects of Mt5178 C/A polymorphism and coffee consumption on the risk of hypertension [16], risk of hyper-LDL cholesterolemia [17] and clustering of cardiovascular risk factors [18]. Amongst men with Mt5178C genotype, the risk of hypertension was significantly lower in those who consumed ≥2 cups of coffee per day than in those who consumed ≤1 cup of coffee per day [16].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of the clustering of cardiovascular risk factors was significantly lower in those who consumed ≥1 cup of coffee per day than in those who consumed <1 cup of coffee per day [18]. Amongst Mt5178A genotypic men, the risk of hyper-LDL cholesterolemia was significantly higher in those who consumed ≥1 cup of coffee per day than in those who consumed <1 cup of coffee per day [17]. Taken together, the present results do not suggest that coffee intake is more beneficial for health in men with Mt5178C than in those with Mt5178A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations